2018
DOI: 10.21608/adjalexu.2018.57626
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Shear Bond Strength of High-Performance Polymers to Its Resin Veneering and to Dentin (In Vitro Study)

Abstract: INTRODUCTION: : Looking through the wide range of prosthetic options High-performance polymers properties. Needs over layering resin veneer, bonded by a special adhesive, this adds an additional challenge to achieve adequate bond strength, also its bonding to tooth structure remains difficult. OBJECTIVES: To evaluate shear bond strength of CAD/CAM High-performance polymers (BioHPP) with its CAD/CAM veneering composite using two different adhesives, as well as to dentin using two types of cements. MATERIALS AND… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…91,96,97 Moreover, the DTK adhesive resin cement was selected in this study due to its ability to enhance chemical bond between adhesive and PEEK as it is MDP-based dual cure adhesive resin cement. 95 The failure mode revealed for PEEK CAD was type 2 which suggests the adequate bond between the treated PEEK surface the cement used (Fig. 9).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…91,96,97 Moreover, the DTK adhesive resin cement was selected in this study due to its ability to enhance chemical bond between adhesive and PEEK as it is MDP-based dual cure adhesive resin cement. 95 The failure mode revealed for PEEK CAD was type 2 which suggests the adequate bond between the treated PEEK surface the cement used (Fig. 9).…”
Section: Discussionmentioning
confidence: 93%
“…[92][93][94] It has been assumed that adhesives containing methylmethacrylate (MMA) and pentaerythritolacrylate (PEITA) along with extra dimethacrylate increased bond strength significantly, as MMA triggered the PEEK surface to swell while dimethacrylate monomers allowed the connection to composite resin through two binding sites represented as carboxyl groups. 42,43,87,95 Many previous studies revealed high bond strength values after the use of Visio.Link on various pretreated PEEK surface. 91,96,97 Moreover, the DTK adhesive resin cement was selected in this study due to its ability to enhance chemical bond between adhesive and PEEK as it is MDP-based dual cure adhesive resin cement.…”
Section: Discussionmentioning
confidence: 99%
“…PEEK is a tooth-colored material [21] with high purity and elasticity (Young`s elastic modulus is about 3-4 GPa), similar to those of human bone [23]. It is radiolucent, non-corrosive, non-toxic, non-allergenic, and stable to heat and sterilization.…”
Section: Peek and Modified Peek -Biohppmentioning
confidence: 99%
“…It is radiolucent, non-corrosive, non-toxic, non-allergenic, and stable to heat and sterilization. It is resistant to hydrolysis and shows good biocompatibility [23]. Another thing that is also important for its application in implant technology is its low water sorption rate and small solubility.…”
Section: Peek and Modified Peek -Biohppmentioning
confidence: 99%
See 1 more Smart Citation